Profiling of Malaysian seaweeds for bioethanol production / Mohammad Javad Hessami - Mohammad Javad , Hessami (2017)
Marine macroalgae (seaweed) biomass has the potential to be an important feedstock for the production of renewable biofuel. The carbohydrate-rich seaweed shows great potential as a competitive feedstock for the production of bioethanol. Seaweeds offer a more economically feasible and environmentally-friendly bioethanol feedstock to the currently utilised corn and sugarcane. Seaweeds produce a variety of polysaccharides that require differing conditions for saccharification to produce sugars that can be fermented to alcohols. The critical step in bioethanol production is the conversion of carbohydrates to fermentable monosaccharides, which takes place via chemical liquefaction by acid hydrolysis or the more environmentally-friendly enzymatic saccharification, or a combination of both. In this study, 29 Malaysian seaweeds (11 green, 10 red and 8 brown seaweeds) were collected from various habitats and analysed for their potential for bioethanol production. The seaweeds’ species were analysed for total carbohydrate content, while sugar production was investigated using the common method of dilute acid hydrolysis. The highest total carbohydrate content was in Kappaphycus alvarezii (71.22 ± 0.71 % DW), followed by Eucheuma denticulatum (69.91 ± 3.35 % DW). The highest reducing sugar content was found in K. alvarezii and Gracilaria manilaensis, which were 34.12 ± 1.09 % DW and 33.02 ± 1.11 % DW, respectively. Two seaweed species, K. alvarezii and G. manilaensis, were selected for further analyses based on their high sugar and carbohydrate contents. To optimise the saccharification process, factors such as temperature, incubation time, and acid concentration were applied, and based on highest reducing sugar yield and acceptable fermentation, inhibitors generated during hydrolysis the combination of 2.5 % w v-1 sulphuric acid, temperature of 120 °C, and 40 min incubation time were selected, which is regarded as milder, but effective parameters for hydrolysis. In the current study, this hydrolysis treatment produced total reducing sugar yields of 34% DW (K. alvarezii) and 33 % DW (G. manilaensis). Two wild-type yeasts, plus one industrial grade yeast (Saccharomyces cerevisiae, Ethanol Red) were used to ferment sugar in this study. Only S. cerevisiae Ethanol Red, resulted in high ethanol yield and was used for further fermentation study. The hydrolysed seaweeds via the optimised method were converted to bioethanol, where S. cerevisiae resulted in bioethanol yields of 20.90 g L-1 (71.0 % of theoretical yield) for K. alvarezii and 18.16 g L-1 (67.9 % theoretical yield) for G. manilaensis. Dilute acid residues of both seaweed species were hydrolysed using enzymatic approach and assimilated to ethanol. The cumulative yield of ethanol of both dilute acid and enzymatic saccharification was 0.14 g g-1 biomass using K. alvarezii, while cumulative ethanol yield of 0.15 g g-1 biomass was achieved using G. manilaensis. In the current study, selected seaweed species were subjected to hydrolysis by dilute acid saccharification under mild condition using response surface method. Obtained results indicate that this new strategy can be effective in the saccharification of macroalgal biomass. This study simultaneously illuminated not only potential seaweed resources of Malaysia as feedstock for biofuel, but also challenges pertaining to this subject.